Efektivitas Isolat Lokal Boyolali sebagai Bakteri Dekomposter The Effectivness of Local Isolate Bacteria from Boyolali as a Decomposter - Yudi Rinanto; Umi Fatmawati (Universitas Sebelas Maret, 2015)
The aim of this research is to identify the effectivness of Local Isolate Bacteria from Boyolali (ILB) to decompose organic materials from wasted vegetable and slurry. The result of decomposition werecompared to EM4 for control. The laboratoryresult indicates that Local isolate bacteria from Boyolali were more effective than EM4 to increase N (Nitrogen) contant. The ability of Local isolate bacteria from Boyolali was better than EM4 in degrading organic materials of slurry, particularly, towardsP (Phosphate). The best concentrationof ILBdecomposition is 30 %. Liquid fertilizer produced from Slurrywithdecomposition ILB 30% that applied towards cabbage increased the weight of cabbage fruit and the length of circumference by 0.5525 gram and 12.67 cm respectively. From the experimental results thatit can be concluded that ILB hasbetter capability in decomposing organic material than EM4. ILB has a good potentialas decomposter toproduces liquid organic fertilizer. Key word: Local isolate, decomposter, EM4, Slurry, cabbage